Tari Telek Nyandar Ati Sebuah Inspirasi dari Tapel Ni Swarni - I Dewa Ayu Galuh Intan Rakasiwi; Gusti Ayu Ketut Suandewi; Kompyang Gede Widnyana (UPT Pusat Penerbitan LP2MPP Institut Seni Indonesia Denpasar, 2022)
Telek dance is a dance that uses tapel, has a smooth character, is identical to using a fan property. Telek Nyandar Ati dance is a work that was born from research. This dance is inspired by a tapel in the Intaran Traditional Village, Sanur Kauh region, namely Tapel Ni Swarni. This dance has its own peculiarities starting from the beginning of the creation, form, and function of the Telek Nyandar Ati Dance. This study uses a qualitative method with an aesthetic and socio-historical approach. Data obtained through observation, structured interviews and unstructured interviews, and indirectly through literature study, as well as documentation. On this occasion the researcher took the MBKM policy for the Research or Research program with the object of research being the Telek Nyandar Ati Dance, an inspiration from Ni Swarni's tape. Telek Nyandar Ati dance is a work inspired by Ni Swarni's tapel. Ni Swarni's tape is the result of Ida Pedande Made Sideman's imagination of a very beautiful woman who he loves very much, namely Ni Swarni, who is his wife. The Telek Nyandar Ati dance is a group dance danced by six dancers consisting of three telek dancers and three male dancers as pengabih. The Telek Nyandar Ati dance is a work that started with a research. It has the following performance structure: metaki-taki, pamahbah, pengawak, pengecet, and ngewaliang pragina. This dance was originally functioned as an idealistic performance, then along with its journey functioned as an accompaniment dance when sesuhunan at the Dalem Pacekan Penestanan Penestanan Temple napak pertiwi. Keywords: Ni Swarni, Nyandar Ati, telek